(untitled) (Journal of Hama University, 2021)
The aim of the current research is to recognize the level of cognitive flexibility among lecturers and students at Hama University, and to know the difference in the level of cognitive flexibility between lecturers and students, as well as to identify the differences in the level of cognitive flexibility among lecturers according to variables (gender, college specialization, age, and years of experience), and the students according to variables (gender, college specialization, and age). The sample consisted of (41) members of the teaching staff, and (376) male and female students. The researcher applied the measure of cognitive flexibility prepared by Abd al-Wahhab 2011, which consisted of (30) items. The research had the following results: - The level of cognitive flexibility among lecturers was high, and the automatic flexibility came in the first place at a very high level, followed by the adaptive flexibility in the second place at a high level. The level of cognitive flexibility among students was high, and the automatic flexibility came in the first place at a high level, followed by the adaptive flexibility in the second place at a high level.There is a statistically significant difference between the average scores of the sample members on the cognitive flexibility scale according to the variable (lecturer, student), in favor of the faculty member on the scale as a whole and on both dimensions.There are no statistically significant differences between the mean scores of the lecturers at Hama University on the measure of cognitive flexibility according to the variables of sex, age, and years of experience, while there is a statistically significant difference according to the variable of the college specialization, in favor of theoretical colleges.There is a statistically significant difference between the mean scores of Hama University students on the scale of cognitive flexibility according to the gender variable, in favor of females on the scale as a whole and on its dimensions, There are no statistically significant differences according to the variables of the college specialization and age.